The Impact of Mentoring and Work Motivation on the Proactivity of Generation Z Employees in Jakarta with Leadership Style as a Moderating Variable - Syukur, Aris Muhamad; Wibowo, Daniel Pungkas Prastia; Usman, Osly (Manunggal Halim Jaya, 2025)
This study examines the impact of mentoring and work motivation on the proactivity of Generation Z employees in Jakarta, with leadership style as a moderating variable. Using a sample of 100 employees and analysis through Partial Least Squares–Structural Equation Modeling (PLS-SEM), the findings reveal that work motivation strongly and positively influences proactivity. Mentoring also demonstrates a positive effect. Interestingly, leadership style significantly strengthens the effect of mentoring, but does not moderate the relationship between work motivation and proactivity. These findings suggest that, to enhance the proactivity of Generation Z employees, organizations should focus on improving intrinsic motivation, optimizing mentoring programs, and implementing a supportive leadership style.